Análise sensorial e instrumental de linhagens de alface Vanda em diferentes tipos de cultivo - Garcia, Gabriel Artur (Universidade Federal de São Carlos, 2023)
The objective of this work was to evaluate ten lettuce strains, one of them being Vanda and nine others developed from it, in three types of cultivation: screened hydroponics, greenhouse hydroponics and field cultivation. Evaluations were made using instrumental analysis of color, total chlorophyll index, sensory analysis of visual preference and purchase intent. The strain with the highest levels of chlorophyll was 4-2-1 and the strain with the best L* value (luminosity) was 176-3-2-1 in hydroponic cultivation in a greenhouse. For the a* value (green coloration), the lineage F9 39-4 was highlighted, also in greenhouse hydroponics. The 4-2-1 line grown in the field presented the highest b* value, which indicates more yellow shades. The highest chroma value (color saturation) was found in the field-grown 4-2-1 line and the highest evaluated hue value was observed in the F10 47-2 line. For the sensory attributes of color and brightness, the strain 1401-141-4 obtained the highest values. For visual texture, it was verified that the strain F10 47-2 in greenhouse obtained better results. For global preference, the grades were higher for lineage F10 206 in greenhouse and, regarding purchase intention, 4-2-1 in screened system. There was interaction between the types of cultivation and the lines.
Sensory and instrumental analysis of Vanda lettuce lines in different types of cultivation
Keywords: Cor; Brilho; Clorofila; Preferência; Color; Bright; Chlorophyll; Preference; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS